An Analysis of Figurative Language in the song lyric of "1989" Album by Taylor Swift - Rike Monike; Eli Diana; Merry Rullyanti (Literary Criticism, 2021)
This study concerns with the descriptive analysis of figurative language in the song lyrics by Taylor Swift's "1989" Album. This research to answer two statement of problem that is(l) what of types of figurative language that is used in the song Lyrics by Taylor Swift's "1989" album? And (II) what the contextual meaning of figurative language in song lyrics by Taylor Swift's "1989" album? And the researcher explains about the review of the related theories and related studies this review is very important because it used as the basis of analysis of the study. The researcher uses a descriptive qualitative method to classify and analyze the sentence. The aim of descriptive qualitative method is to describe a place, fact and characteristic of population systematically, factually and accurately. Descriptive qualitative method employs technique of seeking, collecting and analyzing data. After investigating the sentence in the song lyric, the researcher found several findings of figurative language on it There are seven kinds of figurative language that is used in the song lyrics, they are simile, personification, hyperbole, metaphor, oxymoron, symbol, and synecdoche. The last is the dominant of figurative language that used is metaphor. Keyword: Figurative Language, analyze method, kinds of Figurative language